2021
DOI: 10.1016/j.jad.2021.06.077
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and prediction nomogram model for psychosocial and behavioural problems among children and adolescents during the COVID-19 pandemic: A national multicentre study

Abstract: Background We aimed to explore the risk profiles attributable to psychosocial and behavioural problems during the coronavirus disease 2019 pandemic. To this end, we created a risk-prediction nomogram model. Methods A national multicentre study was conducted through an online questionnaire involving 12,186 children (6-11 years old) and adolescents (12-16 years old). Respondents’ psychosocial and behavioural functioning were assessed using the Achenbach Child Behaviour Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Ten studies examined the impact of the COVID-19 pandemic on eating disorders and disordered eating behaviors in adolescents and/or young people (Chadi et al, 2021 ; Koenig et al, 2021 ; Lin et al, 2021 ; Matthews et al, 2021 ; Muzi et al, 2021 ; Otto et al, 2021 ; Springall et al, 2021 ; Stewart et al, 2021 ; Wang L. et al, 2021 ; Zeiler et al, 2021 ). Five studies used retrospective analysis or chart review to examine eating disorder presentations in hospital or inpatient facilities finding the COVID-19 pandemic was associated with increased visits from young people requiring acute medical intervention (Chadi et al, 2021 ; Lin et al, 2021 ; Matthews et al, 2021 ; Otto et al, 2021 ; Springall et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies examined the impact of the COVID-19 pandemic on eating disorders and disordered eating behaviors in adolescents and/or young people (Chadi et al, 2021 ; Koenig et al, 2021 ; Lin et al, 2021 ; Matthews et al, 2021 ; Muzi et al, 2021 ; Otto et al, 2021 ; Springall et al, 2021 ; Stewart et al, 2021 ; Wang L. et al, 2021 ; Zeiler et al, 2021 ). Five studies used retrospective analysis or chart review to examine eating disorder presentations in hospital or inpatient facilities finding the COVID-19 pandemic was associated with increased visits from young people requiring acute medical intervention (Chadi et al, 2021 ; Lin et al, 2021 ; Matthews et al, 2021 ; Otto et al, 2021 ; Springall et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a meta-analysis by Sharma et al ( 2021 ) reported that the prevalence of sleep disturbances in children and adolescents during the pandemic was 54%. In addition, some authors revealed a significant increase in emotional, social, and behavioral problems (Cost et al, 2021 ; Liu et al, 2021a ; Wang et al, 2021a ). For example, Liu et al ( 2021a ) investigated the prevalence of conduct problems and emotional symptoms, highlighting a significant increase during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The model has been widely used to assess disease risk and prognosis [ 15 ]. Wang et al constructed a nomogram to predict the probability of psychosocial and behavioral problems in children and adolescents from an online questionnaire involving 12,186 children (6–11 years) and adolescents (12–16 years) [ 16 ]. Zhang et al retrospectively analyzed the clinical baseline characteristics of 64 children in China and further created a recurrence risk model of children Neurophyllitis optica spectrum disorders using a nomogram [ 17 ].…”
Section: Discussionmentioning
confidence: 99%